Do Firm Characteristics Influence Integrated Reporting? - Kusumawardani , Natasha Theodora; Ulupui, IGK Agung; Handarini , Dwi Handarini; Sholikah, Badingatus (Indonesian Journal of Accounting and Governance, 2024)
The objective of this study is to examine the influence of the stakeholder pressure, the firm size, and the frequency of audit committee meetings on integrated reporting, all of which serve as the independent variables in this study. In addition, the integrated reporting is used as the dependent variable. The study focuses on the manufacturing industry listed on the Indonesia Stock Exchange during the period of 2017-2019 with 309 samples of data which were selected by using the purposive sampling technique. The results of the multiple linear regression test suggest that the stakeholder pressure and the firm size have a positive influence on integrated reporting, while the frequency of audit committee meetings has no influence on integrated reporting. This indicates that the stakeholders have a major role in the implementation of integrated reporting in companies, and large companies which are categorized based on their total assets can implement better integrated reporting practices. However, the discussion of integrated reporting implementation has not become a priority in the audit committee meetings.